Optical sheet adhesive
Patent Information
- Application Number
- JP2022512166
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-03-30
- Filing Date
- 2021-03-26
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2041-03-26
AI Technical Summary
【0009】 本発明によれば、透明性に優れ、かつ、低温条件下での屈曲性が高い硬化物を与え、さらに、硬化前における形状保持性に優れる光学用シート状接着剤が提供される。
Smart Images

Figure 0007631316000001
Abstract
Description
[Technical field]
[0001] The present invention relates to an optical sheet-like adhesive that gives a cured product that has excellent transparency and high flexibility even under low temperature conditions, and further has excellent shape retention before curing. [Background technology]
[0002] In recent years, various devices such as display devices and light-emitting devices have been made more flexible in order to improve portability, ease of installation, design, visibility, etc. For this reason, there is a demand for adhesives that give cured products with high flexibility as adhesives used in the manufacture of flexible devices.
[0003] Conventionally, sheet-shaped adhesives containing epoxy resins have been used in the manufacture of devices, but the cured products of adhesives containing epoxy resins tend to have a high storage modulus and poor toughness. For example, Patent Document 1 describes a thermosetting adhesive sheet containing an epoxy resin, characterized in that the cured product of the thermosetting adhesive sheet has a storage modulus (x1) of 1 GPa or more at 25°C and a storage modulus (x2) of 1 GPa or more at 100°C.
[0004] As a method for improving the toughness of a cured product of a resin composition containing an epoxy resin, a method of adding fine rubber particles or the like to the resin composition is known. For example, Patent Document 2 describes an epoxy resin composition containing a bisphenol E type epoxy resin, rubber fine particles, and a curing agent. Patent Document 2 also describes that a cured product of the epoxy resin composition has excellent toughness. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2017-110128 A [Patent Document 2] JP 2013-87124 A Summary of the Invention [Problem to be solved by the invention]
[0006] As described in Patent Document 2, the addition of rubber fine particles to a resin composition containing an epoxy resin can improve the toughness and impact resistance of the cured product. However, the cured product of the resin composition containing rubber fine particles tends to be poor in transparency. For this reason, a sheet adhesive containing an excessive amount of rubber fine particles may not be suitable as an optical sheet adhesive. Furthermore, according to the inventors' investigations, even if it is possible to obtain a sheet adhesive that gives a cured product that has excellent transparency and high flexibility under low temperature conditions, it has sometimes been difficult to obtain a sheet adhesive that ensures the cohesiveness of the sheet adhesive before curing and also has excellent shape retention before curing.
[0007] The present invention has been made in consideration of the above-mentioned situation, and aims to provide an optical sheet-like adhesive that gives a cured product that has excellent transparency and high flexibility under low temperature conditions, and further has excellent shape retention before curing. [Means for solving the problem]
[0008] In order to solve the above problems, the present inventors have conducted extensive research into sheet-like adhesives containing a binder resin and an epoxy resin, and have completed the present invention. According to the present invention, there are provided optical sheet-like adhesives as described below in [1] to [8]. [1] An optical sheet adhesive comprising the following components (A) and (B), wherein the storage shear modulus (G'0) of the cured product of the optical sheet adhesive at 0°C is 2×10 7 Optical sheet adhesive with a strength of less than Pa. Component (A): A binder resin component containing a binder resin having a glass transition temperature (Tg) of 50°C or higher. Component (B): An epoxy-based curing component containing a multifunctional epoxy resin [2] The optical sheet-like adhesive according to [1], wherein at least one of the resins constituting the component (A) and having a glass transition temperature (Tg) of 50°C or higher is a phenoxy resin. [3] The optical sheet-like adhesive according to [1] or [2], wherein at least one of the resins constituting the component (A) and having a glass transition temperature (Tg) of 50°C or higher is a polyvinyl acetal resin. [4] The optical sheet-like adhesive according to any one of [1] to [3], wherein at least one of the multifunctional epoxy resins constituting the component (B) is an epoxy resin (BL) that gives a cured product having a glass transition temperature (Tg) of 25°C or lower. [5] The optical sheet-like adhesive according to [4], wherein the content of the epoxy resin (BL) is 50 to 75 mass % based on the entire optical sheet-like adhesive. [6] The optical sheet-like adhesive according to [4] or [5], wherein the epoxy resin (BL) is a multifunctional epoxy resin having an oxyalkylene structure. [7] The optical sheet-like adhesive according to any one of [1] to [6], wherein at least one of the polyfunctional epoxy resins constituting the component (B) is liquid at 23°C. [8] The optical sheet-like adhesive according to any one of [1] to [7], wherein the haze of a cured product of the optical sheet-like adhesive is 1% or less. Effect of the Invention
[0009] According to the present invention, an optical sheet-like adhesive is provided which gives a cured product that has excellent transparency and high flexibility under low temperature conditions, and further has excellent shape retention before curing. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0010] The optical sheet-like adhesive of the present invention is an optical sheet-like adhesive containing the above-mentioned components (A) and (B), and satisfies the requirement for the storage shear modulus of the cured product at 0°C (hereinafter also referred to as the "low temperature modulus requirement"). The sheet-like adhesive refers to an adhesive formed into a sheet that exhibits no fluidity at room temperature (23° C., the same applies below). In the present invention, the sheet-like adhesive may be in the form of a strip or a long strip (strip). In this specification, the "optical sheet adhesive" may be referred to as a "sheet adhesive".
[0011] [Component (A)] The optical sheet-like adhesive of the present invention contains, as component (A), a binder resin component that includes a binder resin (hereinafter sometimes referred to as "binder resin (AH)") having a glass transition temperature (Tg) of 50°C or higher. In the present invention, the term "binder resin component" means the binder resin when the optical sheet adhesive contains one type of binder resin, and means a mixture of two or more types of binder resins when the optical sheet adhesive contains two or more types of binder resins. "Binder resin" refers to a polymer component that imparts shape retention or flexibility to the sheet adhesive.
[0012] An adhesive containing a multifunctional epoxy resin, such as the optical sheet adhesive of the present invention, may not be able to maintain a certain shape in an uncured state. In particular, in the optical sheet adhesive of the present invention, as the content ratio of component (B) increases, the optical sheet adhesive can be cured more significantly (i.e., a cured product with higher hardness can be obtained), but as the content ratio of component (B) increases, the shape retention of the optical sheet adhesive further decreases. In the present invention, component (A) is utilized to solve this problem. That is, the optical sheet-like adhesive of the present invention contains component (A) and therefore has sufficient shape retention even when it contains a large amount of component (B).
[0013] The component (A) is composed only of a binder resin, and contains at least the binder resin (AH) as an essential component. The component (A) may be composed only of the binder resin (AH), or may further contain, in addition to the binder resin (AH), a binder resin having a glass transition temperature (Tg) of less than 50°C. However, it is preferable that the component (A) is composed only of the binder resin (AH).
[0014] The binder resin (AH) is not particularly limited as long as it has a glass transition temperature (Tg) of 50° C. or higher and is a polymer component that imparts shape retention or flexibility to the optical sheet-like adhesive. The glass transition temperature (Tg) of the binder resin (AH) is 50° C. or higher, and preferably 80° C. or higher. There is no particular upper limit, but it is usually 200° C. or lower.
[0015] The glass transition temperature (Tg) of the binder resin (AH) can be measured in accordance with JIS K 7121 using a differential scanning calorimeter.
[0016] If component (A) does not contain a binder resin (AH), the shape retention of the optical sheet adhesive is insufficient, and for example, when a release sheet is peeled off to use the optical sheet adhesive, the optical sheet adhesive may be destroyed. In other words, an optical sheet adhesive that does not contain a binder resin (AH) has poor shape retention before curing. From this viewpoint, the content of the binder resin (AH) is preferably 20 to 45% by mass, and more preferably 25 to 43% by mass, based on the total mass of the optical sheet-like adhesive.
[0017] The weight average molecular weight (Mw) of the binder resin (AH) is preferably 10,000 to 300,000, and more preferably 30,000 to 200,000. The weight average molecular weight (Mw) of the binder resin (AH) can be determined in terms of standard polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a solvent.
[0018] Examples of the binder resin (AH) include olefin resins, acrylic polymers, polyester resins, polyvinyl alcohol resins, polyvinyl acetal resins, polyvinyl chloride, phenoxy resins, polyamide resins, cellulose-based materials, polyvinyl ethers, polyimide resins, styrene-isoprene-styrene block copolymers, and styrene-butadiene-styrene block copolymers. The binder resin (AH) can be used alone or in combination of two or more kinds.
[0019] At least one of the binder resins (AH) is preferably a phenoxy resin. Phenoxy resin is a polymer whose main chain is a polyaddition structure of aromatic diol and aromatic diglycidyl ether. Phenoxy resin generally corresponds to a high molecular weight epoxy resin, and refers to one with a degree of polymerization of about 100 or more.
[0020] Some phenoxy resins have a high glass transition temperature (Tg), and such phenoxy resins are suitably used as the binder resin (AH).
[0021] The epoxy equivalent of the phenoxy resin is preferably 5,000 g / eq or more, more preferably 7,000 g / eq or more. The epoxy equivalent value can be measured in accordance with JIS K7236 (the same applies below).
[0022] Examples of the phenoxy resin include bisphenol A type phenoxy resin, bisphenol F type phenoxy resin, bisphenol S type phenoxy resin, copolymer type phenoxy resin of bisphenol A type and bisphenol F type, bisphenol E type phenoxy resin, naphthalene type phenoxy resin, novolac type phenoxy resin, biphenyl type phenoxy resin, and cyclopentadiene type phenoxy resin. These phenoxy resins can be used alone or in combination of two or more.
[0023] The phenoxy resin can be obtained by a method of reacting a difunctional phenol with an epihalohydrin to a high molecular weight, or by a method of subjecting a difunctional epoxy resin with a difunctional phenol to a polyaddition reaction. For example, the phenoxy resin can be obtained by reacting a bifunctional phenol with an epihalohydrin in the presence of an alkali metal hydroxide in an inert solvent at a temperature of 40 to 120° C. The phenoxy resin can also be obtained by subjecting a bifunctional epoxy resin and a bifunctional phenol to a polyaddition reaction in the presence of a catalyst such as an alkali metal compound, an organic phosphorus compound, or a cyclic amine compound in an organic solvent having a boiling point of 120° C. or higher, such as an amide solvent, an ether solvent, a ketone solvent, a lactone solvent, or an alcohol solvent, by heating to 50 to 200° C. at a reaction solids concentration of 50% by weight or less.
[0024] The bifunctional phenols are not particularly limited as long as they are compounds having two phenolic hydroxyl groups. For example, monocyclic bifunctional phenols such as hydroquinone, 2-bromohydroquinone, resorcinol, and catechol; bisphenols such as bisphenol A, bisphenol F, bisphenol AD, and bisphenol S; dihydroxybiphenyls such as 4,4'-dihydroxybiphenyl; dihydroxyphenyl ethers such as bis(4-hydroxyphenyl)ether; and those in which a linear alkyl group, a branched alkyl group, an aryl group, a methylol group, an allyl group, a cyclic aliphatic group, a halogen (such as tetrabromobisphenol A), or a nitro group has been introduced into the aromatic ring of the phenol skeleton; and polycyclic bifunctional phenols in which a linear alkyl group, a branched alkyl group, an allyl group, an allyl group with a substituent, a cyclic aliphatic group, or an alkoxycarbonyl group has been introduced into the carbon atom in the center of the bisphenol skeleton.
[0025] Examples of epihalohydrin include epichlorohydrin, epibromohydrin, and epiiodohydrin.
[0026] In the present invention, commercially available phenoxy resins can also be used, such as YX7200 (glass transition temperature (Tg): 150° C.) and YX6954 (bisphenolacetophenone skeleton-containing phenoxy resin, glass transition temperature (Tg): 130° C.) manufactured by Mitsubishi Chemical Corporation, and YP70 (glass transition temperature (Tg): 70° C.) manufactured by Nippon Steel Chemical & Material Co., Ltd.
[0027] At least one of the binder resins (AH) is preferably a polyvinyl acetal resin. Polyvinyl acetal resin is a polymer obtained by an acetalization reaction between the hydroxyl groups of polyvinyl alcohol (or a partially saponified product of its ester; the same applies below) and an aldehyde.
[0028] In order to obtain a photocurable sheet adhesive that gives a cured product with superior adhesive strength, it is preferable that the optical sheet adhesive contains a large amount of component (B). However, optical sheet adhesives that contain a large amount of component (B) tend to have reduced uniformity of the components, which may result in reduced transparency of the obtained cured product. The use of polyvinyl acetal resin as the binder resin (AH) can improve the uniformity of the components, making it easier to obtain an optical sheet-like adhesive that gives a cured product with excellent coatability.
[0029] Furthermore, when a phenoxy resin is used as the binder resin (AH), a decrease in the uniformity of the components can occur. However, when component (A) contains both a phenoxy resin and a polyvinyl acetal resin, the uniformity of the components of the adhesive for optical sheets can be improved.
[0030] Examples of the polyvinyl acetal resin include polyvinyl butyral obtained by reacting polyvinyl alcohol with butylaldehyde, polyvinyl formal obtained by reacting polyvinyl alcohol with formaldehyde, and polyvinyl acetoacetal obtained by reacting polyvinyl alcohol with acetaldehyde. These polyvinyl acetal resins can be used alone or in combination of two or more.
[0031] Polyvinyl acetal resin can be synthesized by reacting polyvinyl alcohol with aldehyde in a suitable solvent using an acid catalyst, such as water, alcoholic solvents such as methyl alcohol and ethyl alcohol, mixed solvents of water and alcohol, and aprotic polar solvents such as dimethyl sulfoxide.
[0032] Alternatively, the polyvinyl acetal resin can be synthesized by adding an acid catalyst and an aldehyde to a polyvinyl acetate solution and reacting them. The acid catalyst to be used is not particularly limited, and examples thereof include organic acids such as acetic acid, paratoluenesulfonic acid, etc.; and inorganic acids such as nitric acid, sulfuric acid, etc. The reaction is stopped by adding an alkali. The alkali to be used is not particularly limited, and examples thereof include metal hydroxides such as sodium hydroxide and potassium hydroxide, ammonia, metal nitrates such as sodium nitrate, metal carbonates such as sodium carbonate and potassium carbonate, and metal hydrogen carbonates such as sodium hydrogen carbonate and potassium hydrogen carbonate.
[0033] [(B) component] The optical sheet-like adhesive of the present invention contains, as component (B), an epoxy-based curable component that contains a polyfunctional epoxy resin (hereinafter sometimes referred to as "epoxy resin (BP)"). In the present invention, the term "epoxy-based curable component" means an epoxy resin when the optical sheet-like adhesive contains one type of epoxy resin, and means a mixture of those epoxy resins when the optical sheet-like adhesive contains two or more types of epoxy resins. The term "multifunctional epoxy resin" refers to an epoxy resin having two or more epoxy groups in the molecule. In addition, even if a compound has an epoxy group, if it corresponds to the binder resin constituting component (A), it is not considered to constitute component (B).
[0034] The optical sheet adhesive containing component (B) has curing properties, and the cured product of the optical sheet adhesive has a certain degree of hardness even under high temperature conditions (for example, 100° C.).
[0035] The content of component (B) is preferably 50 to 75 mass %, more preferably 52 to 70 mass %, and even more preferably 54 to 65 mass %, based on the total mass of the optical sheet-like adhesive. By ensuring that the content of component (B) is within the above range, it becomes easier to obtain an optical sheet-like adhesive whose cured product has a certain degree of hardness even under high temperature conditions. Furthermore, the shape retention and tackiness of the optical sheet-like adhesive, as well as the shape retention of the cured product under high temperature conditions, are maintained in a well-balanced manner.
[0036] The component (B) is composed only of an epoxy resin, and contains at least an epoxy resin (BP) as an essential component. The (B) component may be composed only of the epoxy resin (BP), or may further contain a monofunctional epoxy resin in addition to the epoxy resin (BP). However, it is preferable that the (B) component is composed only of the epoxy resin (BP). The content of the epoxy resin (BP) constituting the component (B) (when there are two or more types of epoxy resin (BP), the total amount of them) is usually 90 to 100 mass%, and preferably 95 to 100 mass%, of the entire component (B). When the content of the epoxy resin (BP) is 90 mass % or more based on the total mass of the component (B), it becomes easier to obtain an optical sheet-like adhesive in which the cured product has a certain degree of hardness even under high temperature conditions.
[0037] The weight average molecular weight (Mw) of the epoxy resin (BP) is preferably 100 to 5,000, and more preferably 200 to 4,000. The weight average molecular weight (Mw) of an epoxy resin (BP) can be determined in terms of standard polystyrene by gel permeation chromatography (GPC) using tetrahydrofuran (THF) as a solvent.
[0038] The epoxy equivalent of the epoxy resin (BP) is preferably 100 g / eq or more and 500 g / eq or less, more preferably 115 g / eq or more and 450 g / eq or less. By curing an optical sheet-like adhesive containing an epoxy resin (B) having an epoxy equivalent of 100 g / eq or more and 500 g / eq or less, a cured product with excellent adhesive strength can be obtained.
[0039] Examples of the epoxy resin (BP) include aliphatic epoxy compounds (excluding alicyclic epoxy compounds), aromatic epoxy compounds, and alicyclic epoxy compounds.
[0040] Examples of the aliphatic epoxy compound include 1,4-butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, triglycidyl ether of glycerin, triglycidyl ether of trimethylolpropane, tetraglycidyl ether of sorbitol, hexaglycidyl ether of dipentaerythritol, diglycidyl ether of polyethylene glycol, and diglycidyl ether of polypropylene glycol.
[0041] Examples of aromatic epoxy compounds include glycidyl ethers of bisphenol A, bisphenol F, or compounds obtained by further adding alkylene oxide to these compounds, and epoxy novolac resins; polyglycidyl ethers of aromatic compounds having two or more phenolic hydroxyl groups, such as resorcinol, hydroquinone, and catechol; glycidyl ethers of aromatic compounds having two or more alcoholic hydroxyl groups, such as phenyldimethanol, phenyldiethanol, and phenyldibutanol; and glycidyl esters of polybasic aromatic compounds having two or more carboxylic acids, such as phthalic acid, terephthalic acid, and trimellitic acid.
[0042] Examples of the alicyclic epoxy compound include polyglycidyl ethers of polyhydric alcohols having at least one alicyclic structure, such as dicyclopentadiene dimethanol diglycidyl ether and hydrogenated bisphenol A, and cycloalkene oxide compounds, such as cyclohexene oxide and cyclopentene oxide-containing compounds obtained by epoxidizing cyclohexene or cyclopentene ring-containing compounds with an oxidizing agent.
[0043] These epoxy resins (BP) can be used alone or in combination of two or more.
[0044] At least one of the epoxy resins (BP) is preferably one that gives a cured product having a glass transition temperature (Tg) of 25° C. or lower (hereinafter, this may be referred to as "epoxy resin (BL)". In other words, the epoxy resin (BL) is one that gives a cured product having a glass transition temperature (Tg) of 25° C. or lower when fully cured alone or in the presence of a curing agent or the like). The epoxy resin (BL) is preferably one that gives a cured product having a glass transition temperature (Tg) of -5° C. or lower, and more preferably one that gives a cured product having a glass transition temperature (Tg) of -20° C. or lower. By using the (B) component containing the epoxy resin (BL), it becomes easier to obtain an optical sheet adhesive that gives a cured product with a low storage shear modulus (G') even under low temperature conditions. Therefore, the optical sheet adhesive containing the epoxy resin (BL) easily satisfies the low temperature modulus requirement. Therefore, it becomes easier to obtain an optical sheet adhesive that has excellent flexibility under low temperature conditions (e.g., 0°C).
[0045] When the optical sheet-like adhesive of the present invention contains an epoxy resin (BL), the content of the epoxy resin (BL) is preferably 50 to 75 mass % of the entire optical sheet-like adhesive, more preferably 52 to 70 mass %, and even more preferably 54 to 65 mass %. When the content of the epoxy resin (BL) is 50 mass % or more based on the entire optical sheet adhesive, it becomes easier to obtain an optical sheet adhesive that satisfies the above-mentioned low-temperature elastic modulus requirement.
[0046] The glass transition temperature (Tg) of the cured product of the epoxy resin (BP) can be determined by differential scanning calorimetry using a sample obtained by performing a curing reaction under conditions that sufficiently cure the epoxy resin (BP). Examples of sample preparation conditions (curing conditions of the epoxy resin (BP)) include the conditions described in the Examples.
[0047] The epoxy resin (BL) may be a polyfunctional epoxy resin having an oxyalkylene structure. Polyfunctional epoxy resins having an oxyalkylene structure tend to give a cured product with a relatively low glass transition temperature (Tg), and are therefore preferably used as the epoxy resin (BL).
[0048] Examples of the oxyalkylene structure include an oxymethylene group, an oxyethylene group, an oxypropylene group, an oxytrimethylene group, an oxybutylene group, an oxypentylene group, an oxyhexylene group, an oxyheptylene group, an oxyoctylene group, an oxynonylene group, an oxydecylene group, an oxyundecylene group, an oxydodecylene group, an oxytridecylene group, an oxytetradecylene group, an oxypentadecylene group, an oxycyclopropylene group, an oxycyclobutylene group, an oxycyclopentylene group, an oxycyclohexylene group, an oxydecahydronaphthalene group, an oxynorbornanylene group, and an oxyadamantanylene group.
[0049] At least one of the epoxy resins (BP) is preferably liquid at 23°C. "Liquid at 23° C." means that it has fluidity at 23° C. The epoxy resin (BP) preferably has a viscosity of 2 to 10,000 mPa·s as measured at 23° C. and 1.0 rpm using an E-type viscometer. By using an epoxy resin (BP) that is liquid at 23° C., it is possible to obtain an optical sheet adhesive that has a low elastic modulus at room temperature. Because such an optical sheet adhesive has excellent application properties at room temperature, there is no need to heat the optical sheet adhesive to soften it during the application process.
[0050] When the optical sheet-like adhesive of the present invention contains an epoxy resin (BP) that is liquid at 23°C, the content of the epoxy resin (BP) that is liquid at 23°C is preferably 50 to 75 mass% of the entire optical sheet-like adhesive, more preferably 52 to 70 mass%, and even more preferably 54 to 65 mass%. When the content of the epoxy resin (B) that is liquid at 23° C. is within the above range, it becomes easier to obtain an optical sheet adhesive having the above-mentioned properties.
[0051] From the viewpoints of facilitating the production of an optical sheet-like adhesive that gives a cured product having a low storage shear modulus (G') even under low temperature conditions, and of improving the application properties of the optical sheet-like adhesive, it is preferable that the epoxy resin (BL) is liquid at 23°C.
[0052] [(C) component] The optical sheet-like adhesive of the present invention may contain a cationic polymerization initiator as component (C). A cationic polymerization initiator is preferred because it efficiently advances the polymerization reaction of the component (B) and can improve the storage stability of the optical sheet-like adhesive compared to other curing agents. Examples of the cationic polymerization initiator include a thermal cationic polymerization initiator and a photo-cationic polymerization initiator. The photo-cationic polymerization initiator is preferred because it can improve the storage stability of the adhesive and the polymerization reaction proceeds quickly after irradiation with light.
[0053] A photocationic polymerization initiator is a compound that generates cationic species when irradiated with ultraviolet light and initiates the curing reaction of a cationic curable compound. It consists of a cationic moiety that absorbs ultraviolet light and an anionic moiety that serves as an acid generating source.
[0054] Examples of the photocationic polymerization initiator include sulfonium salt compounds, iodonium salt compounds, phosphonium salt compounds, ammonium salt compounds, diazonium salt compounds, selenium salt compounds, oxonium salt compounds, bromine salt compounds, etc. Among these, sulfonium salt compounds are preferred because of their excellent compatibility with other components, and aromatic sulfonium salt compounds having an aromatic group are more preferred.
[0055] Examples of sulfonium salt compounds include triphenylsulfonium hexafluorophosphate, triphenylsulfonium hexafluoroantimonate, triphenylsulfonium tetrakis(pentafluorophenyl)borate, 4,4'-bis[diphenylsulfonio]diphenylsulfide-bishexafluorophosphate, 4,4'-bis[di(β-hydroxyethoxy)phenylsulfonio]diphenylsulfide-bishexafluoroantimonate, 7-[di(p-tolyl)phenylsulfonate, 7-[di(β ... 7-[di(p-toluyl)sulfonio]-2-isopropylthioxanthone hexafluorophosphate, 7-[di(p-toluyl)sulfonio]-2-isopropylthioxanthone hexafluoroantimonate, 7-[di(p-toluyl)sulfonio]-2-isopropyltetrakis(pentafluorophenyl)borate, phenylcarbonyl-4'-diphenylsulfonio-diphenylsulfide-hexafluorophosphate, phenylcarbonyl-4'-diphenylsulfonio-diphenylsulfide 4-tert-butylphenylcarbonyl-4'-diphenylsulfonio-diphenylsulfide-hexafluoroantimonate, 4-tert-butylphenylcarbonyl-4'-diphenylsulfonio-diphenylsulfide-hexafluorophosphate, 4-tert-butylphenylcarbonyl-4'-diphenylsulfonio-diphenylsulfide-hexafluoroantimonate, 4-tert-butylphenylcarbonyl-4'-diphenylsulfonio-diphenylsulfide-tetrakis(pentafluorophenyl)borate, 4-(phenylthio)phenyldiphenylsulfonium hexafluoroantimonate, 4-(phenylthio)phenyldiphenylsulfonium hexafluorophosphate, 4-{4-(2-chlorobenzoyl)phenylthio}phenylbis(4-fluorophenyl)sulfonium hexafluoroantimonate, thiophenyldiphenylsulfonium hexafluoroantimonate halide, 4,4',4''-tri(β-hydroxyethoxyphenyl)sulfonium hexafluoroantimonate, 4,Examples of such salts include 4'-bis[diphenylsulfonio]diphenylsulfide-bishexafluoroantimonate, diphenyl[4-(phenylthio)phenyl]sulfonium trifluorotrispentafluoroethylphosphate, tris[4-(4-acetylphenylsulfanyl)phenyl]sulfonium tris[(trifluoromethyl)sulfonyl]methanide, and salts in which the cation moiety is 4-(phenylthio)phenyldiphenylsulfonium and the anion moiety is a phosphorus-based anion to which fluorine and a perfluoroalkyl group are added.
[0056] Examples of iodonium salt compounds include diphenyliodonium tetrakis(pentafluorophenyl)borate, diphenyliodonium hexafluorophosphate, diphenyliodonium hexafluoroantimonate, di(4-nonylphenyl)iodonium hexafluorophosphate, (tricumyl)iodonium tetrakis(pentafluorophenyl)borate, and the like.
[0057] Examples of the phosphonium salt compounds include tri-n-butyl(2,5-dihydroxyphenyl)phosphonium bromide and hexadecyltributylphosphonium chloride.
[0058] Examples of the ammonium salt compound include benzyltrimethylammonium chloride, phenyltributylammonium chloride, and benzyltrimethylammonium bromide.
[0059] The cationic polymerization initiators can be used alone or in combination of two or more. When the optical sheet-like adhesive contains a cationic polymerization initiator, the content of the cationic polymerization initiator is preferably 0.1 to 6 parts by mass, more preferably 0.3 to 5 parts by mass, and even more preferably 0.5 to 4 parts by mass, per 100 parts by mass of component (A).
[0060] The optical sheet adhesive may contain a reactive curing agent other than the cationic polymerization initiator. Examples of the reactive curing agent other than the cationic polymerization initiator include amine compounds such as benzylmethylamine and 2,4,6-trisdimethylaminomethylphenol; imidazole compounds such as 2-methylimidazole, 2-ethyl-4-methylimidazole, and 2-heptadecylimidazole; Lewis acids such as boron trifluoride-monoethylamine complex and boron trifluoride-piperazine complex; and peroxides such as di(t-butylperoxy)diisopropylbenzene; and other heat-reactive curing agents.
[0061] [Other ingredients] The optical sheet-like adhesive of the present invention may contain other components as long as the effects of the present invention are not impaired. Examples of other components include additives such as silane coupling agents, ultraviolet absorbers, antistatic agents, light stabilizers, antioxidants, resin stabilizers, fillers, pigments, extenders, and softeners. These may be used alone or in combination of two or more. When the sheet adhesive of the present invention contains these additives, the content thereof can be appropriately determined depending on the purpose.
[0062] [Layer structure of optical sheet adhesive] The thickness of the optical sheet-like adhesive of the present invention is usually 1 to 50 μm, preferably 1 to 40 μm, and more preferably 2 to 30 μm. The thickness of the optical sheet-like adhesive can be measured using a known thickness meter in accordance with JIS K 7130 (1999). In addition, when the optical sheet-like adhesive has a release film described below, the thickness of the optical sheet-like adhesive is the thickness excluding the thickness of the release film.
[0063] From the viewpoint of protection from the external environment, the optical sheet-like adhesive of the present invention preferably has a release film on at least one surface, and may have release films on both surfaces.
[0064] The optical sheet adhesive of the present invention having a release film on at least one side represents the state before use, and when using the optical sheet adhesive of the present invention, the release film is usually peeled off and removed. When the optical sheet adhesive has release films on both sides, the release film with the lower release strength is usually peeled off and removed first.
[0065] As the release film, a resin film can usually be used. Examples of the resin component of the resin film include polyimide, polyamide, polyamideimide, polyphenylene ether, polyether ketone, polyether ether ketone, polyolefin, polyester, polycarbonate, polysulfone, polyether sulfone, polyphenylene sulfide, polyarylate, acrylic resin, cycloolefin polymer, aromatic polymer, polyurethane polymer, etc. Among these, polyester resin is preferable.
[0066] When the release film has a release agent layer, examples of the release agent include rubber-based elastomers such as silicone-based resins, olefin-based resins, isoprene-based resins, and butadiene-based resins, long-chain alkyl-based resins, alkyd-based resins, and fluorine-based resins.
[0067] The thickness of the release film is usually 10 to 300 μm, preferably 10 to 200 μm, and more preferably 15 to 100 μm.
[0068] [Method for producing optical sheet adhesive] The method for producing the optical sheet adhesive of the present invention is not particularly limited. For example, the optical sheet adhesive can be produced by a casting method.
[0069] The method for producing an optical sheet-like adhesive by casting involves applying the adhesive composition as a raw material to a release film using a known method, and drying the resulting coating to obtain an optical sheet-like adhesive with a release film.
[0070] The adhesive composition contains the above-mentioned components (A) and (B), and, if necessary, other components. The adhesive composition may further contain a solvent. Examples of the solvent include aromatic hydrocarbon solvents such as benzene and toluene; ester solvents such as ethyl acetate and butyl acetate; ketone solvents such as acetone, methyl ethyl ketone and methyl isobutyl ketone; aliphatic hydrocarbon solvents such as n-pentane, n-hexane and n-heptane; and alicyclic hydrocarbon solvents such as cyclopentane, cyclohexane and methylcyclohexane. These solvents can be used alone or in combination of two or more. When the adhesive composition contains a solvent, the content of the solvent can be appropriately determined taking into consideration the coatability and the like. The adhesive composition can be prepared by appropriately mixing and stirring the respective components according to a conventional method.
[0071] The release film used in the production of the optical sheet-like adhesive functions as a support during the production process of the optical sheet-like adhesive, and also functions as a release film for the above-mentioned optical sheet-like adhesive until the optical sheet-like adhesive is used.
[0072] Examples of the method for applying the adhesive composition include spin coating, spray coating, bar coating, knife coating, roll coating, blade coating, die coating, and gravure coating.
[0073] Methods for drying the coating of the adhesive composition include conventionally known drying methods such as hot air drying, heated roll drying, and infrared irradiation. The coating film is dried under conditions of, for example, 80 to 150° C. for 30 seconds to 5 minutes.
[0074] [Characteristics of optical sheet adhesives] When the optical sheet adhesive of the present invention is photocurable, the optical sheet adhesive can be cured, for example, by irradiating the optical sheet adhesive with ultraviolet light. Specific examples of the ultraviolet light source include light sources such as ultra-high pressure mercury lamps, high pressure mercury lamps, low pressure mercury lamps, carbon arc lamps, black light fluorescent lamps, metal halide lamps, etc. The wavelength of the ultraviolet light to be irradiated may be in the wavelength range of 190 to 380 nm. The type, dose, and duration of irradiation of ultraviolet light can be appropriately determined depending on the components of the sheet adhesive to be irradiated and the content of each component. The irradiation intensity is 20 to 1000 mW / cm 2 , light intensity 50~3000mJ / cm 2 degree is preferred.
[0075] When the optical sheet-like adhesive of the present invention is thermosetting, the conditions for thermally curing the optical sheet-like adhesive are not particularly limited. The heating temperature is from 80 to 200°C, and preferably from 90 to 190°C, from the viewpoint of efficiently proceeding with the reaction of the component (B). The heating time is usually from 30 minutes to 12 hours, preferably from 1 to 6 hours.
[0076] The optical sheet adhesive of the present invention has a storage shear modulus (G') at 100°C of a cured product of the optical sheet adhesive. 100 ) but 1×10 5 It is preferable that the pressure is 1 Pa or more.
[0077] An optical sheet adhesive that satisfies these requirements gives a cured product that is resistant to thermal deformation even under high temperature conditions (e.g., 100°C), and is therefore suitable for use as an adhesive for devices that require heat resistance. Furthermore, a cured product that exhibits a high storage modulus at such high temperatures does not soften even at high temperatures, and its adhesiveness is not likely to decrease even when the temperature changes. From this perspective, the storage shear modulus (G') of the cured optical sheet adhesive at 100°C 100 ) is preferably 2 × 10 5Pa or more, more preferably 5×10 5 Pa or more. In addition, the storage shear modulus (G') of the cured optical sheet adhesive at 100°C 100 ) is not particularly limited, but since the optical sheet adhesive of the present invention satisfies the low-temperature elastic modulus requirement and the storage shear elastic modulus at 100°C usually does not exceed the storage shear elastic modulus at 0°C, it is preferred that the upper limit be 2×10 7 Pa or less.
[0078] Storage shear modulus of the cured product at 100°C (G' 100 ) but 1×10 5 An optical sheet adhesive having a viscosity of 0.1 Pa or more can be efficiently obtained by incorporating a large amount of component (B) in the optical sheet adhesive.
[0079] The optical sheet adhesive of the present invention satisfies the above-mentioned low-temperature elastic modulus requirement. That is, the storage shear modulus (G'0) of the cured optical sheet adhesive at 0°C is 2×10 7 Pa or less.
[0080] Optical sheet adhesives that satisfy the low-temperature elastic modulus requirements give cured products that are highly flexible not only under high temperature conditions but also under low temperature conditions (for example, 0° C.), and are therefore suitable for use as adhesives for flexible devices. From this viewpoint, the storage shear modulus (G'0) at 0°C of the cured product of the optical sheet adhesive is preferably 1.5×10 7 Pa or less, and more preferably 1.2×10 7 Pa or less. In addition, although there is no particular lower limit for the storage shear modulus (G'0) of the cured product of the optical sheet adhesive at 0°C, as described above, the optical sheet adhesive of the present invention has a storage shear modulus (G'0) of the cured product at 100°C. 100 ) but 1×10 5 The storage shear modulus at 0°C is preferably 1×10 Pa or more. Since the storage shear modulus at 0°C is usually not lower than the storage shear modulus at 100°C, 5 It is preferable that the pressure is 1 Pa or more.
[0081] An optical sheet adhesive that gives a cured product that has a low storage shear modulus at low temperatures and satisfies the low-temperature modulus requirements can be efficiently obtained by incorporating an epoxy resin (BL) in the optical sheet adhesive.
[0082] As described above, the cured product of the optical sheet-like adhesive of the present invention satisfies the low-temperature elastic modulus requirement. In addition, the storage shear elastic modulus (G') of the cured product of the optical sheet-like adhesive at 100°C 100 ) but 1×10 5 It is preferable that the pressure is 1 Pa or more. In this case, the storage shear modulus (G') of the cured product of the optical sheet adhesive of the present invention is usually 1×10 5 ~2×10 7 Pa. This range of storage shear modulus (G') is narrower than the range of storage shear modulus (G') of a cured product of a conventional sheet adhesive containing an epoxy resin. For example, the cured product of the optical sheet adhesive of the present invention has a storage shear modulus at 0°C (G'0) and a storage shear modulus at 100°C (G' 100 ) ratio value (G'0 / G' 100 ) is usually 1 to 20, and preferably 1.2 to 15. Thus, if the optical sheet adhesive of the present invention provides a cured product with little variation in storage shear modulus (G') over the range from low temperatures (near 0°C) to high temperatures (near 100°C) (i.e., a cured product with little difference between flexibility under low temperature conditions and flexibility under high temperature conditions), it can be suitably used as an adhesive for devices used in environments with large temperature changes.
[0083] The storage shear modulus (G') of the cured product of the optical sheet-like adhesive can be measured by the method described in the Examples. The measurement samples can be prepared using appropriate curing conditions depending on the properties of each optical sheet adhesive, and the same applies to the measurement samples used when measuring the total light transmittance and haze described below. For example, when the optical sheet adhesive is photocurable, a measurement sample can be prepared under the conditions described in the Examples.
[0084] The optical sheet-like adhesive of the present invention can improve the flexibility of the cured product by adjusting the type and amount of resin contained in component (A) and the type and amount of resin contained in component (B), and does not require any component that reduces transparency. Therefore, the optical sheet-like adhesive of the present invention has excellent transparency.
[0085] The total light transmittance of the cured product of the optical sheet-like adhesive of the present invention is preferably 90% or more, and more preferably 95% or more. The total light transmittance of the cured product of the optical sheet-like adhesive can be measured in accordance with JIS K7361-1:1997.
[0086] The haze of the cured product of the optical sheet-like adhesive of the present invention is preferably 1% or less, and more preferably 0.5% or less. The haze of the cured product of the optical sheet-like adhesive can be measured in accordance with JIS K7136:2000.
[0087] [Applications of optical sheet adhesives] As described above, the optical sheet-like adhesive of the present invention provides a cured product that has excellent transparency and high flexibility under low temperature conditions, and further has excellent shape retention before curing. Therefore, the optical sheet-like adhesive of the present invention is suitable for use in producing optical devices equipped with light-emitting elements, light-receiving elements, display elements, etc. Examples of optical devices include organic electroluminescence (EL) displays, organic electroluminescence (EL) lighting, liquid crystal displays, solar cells, and electronic paper. EXAMPLES
[0088] The present invention will be described in more detail below with reference to examples, although the present invention is not limited to the following examples in any way.
[0089] [Compounds used in the Examples and Comparative Examples] Binder resin (AH1): Phenoxy resin [manufactured by Mitsubishi Chemical Corporation, product name: YX7200B35, glass transition temperature (Tg): 150°C, Mw: 30,000] Binder resin (AH2): Polyvinyl acetal resin (manufactured by Sekisui Chemical Co., Ltd., product name: S-LEC KS-5Z, glass transition temperature (Tg): 113°C, Mw: 130,000) Binder resin (AH3): Polyvinyl acetal resin (manufactured by Sekisui Chemical Co., Ltd., product name: S-LEC BX-25Z, glass transition temperature (Tg): 86°C, degree of polymerization: 2,300) Binder resin (AH4): Phenoxy resin (manufactured by Nippon Steel Chemical & Material Co., Ltd., product name: YP70, glass transition temperature (Tg): 70°C, Mw: 55,000) Binder resin (A1): Phenoxy resin [manufactured by Mitsubishi Chemical Corporation, product name: YX7180BH40, glass transition temperature (Tg): 15°C, Mw: 40,000] Epoxy resin (BL1): Epoxy resin with oxyalkylene groups (liquid at 23°C) [manufactured by Mitsubishi Chemical Corporation, product name: YX7400, epoxy equivalent: 440g / eq, glass transition temperature (Tg) of cured product: -69°C] Epoxy resin (BL2): Epoxy resin with oxyalkylene groups (liquid at 23°C) [ADEKA, product name: ED-506, epoxy equivalent: 300g / eq, glass transition temperature (Tg) of cured product: -50.7°C] Epoxy resin (BP1): Hydrogenated bisphenol A type epoxy resin (liquid at 23°C) [manufactured by Mitsubishi Chemical Corporation, product name: YX8000, epoxy equivalent: 205g / eq, glass transition temperature (Tg) of cured product: 96.4°C] Epoxy resin (BP2): Epoxy resin (liquid at 23°C) [manufactured by Daicel Corporation, product name: Celloxide 2021P, epoxy equivalent: 128-145g / eq, glass transition temperature (Tg) of cured product: 94.5°C] Cationic polymerization initiator (C1): Photocationic polymerization initiator, 4-(phenylthio)phenyldiphenylsulfonium hexafluorophosphate [manufactured by San-Apro Co., Ltd., product name: CPI-100P]
[0090] The glass transition temperature (Tg) of the cured product of the epoxy resin constituting component (B) was measured by the following method. (Preparation of measurement samples) 0.5 parts by mass of a thermal cationic polymerization initiator (manufactured by Sanshin Chemical Industry Co., Ltd., product name: SI-B3A) was added to 100 parts by mass of each epoxy resin. The resulting mixture was poured into a polytetrafluoroethylene mold with a thickness of 1 mm and a size of 20 mm x 20 mm, and cured by heating at 100°C for 60 minutes to obtain a cured product (measurement sample). (Differential Scanning Calorimetry) Differential scanning calorimetry was carried out using a differential scanning calorimeter (manufactured by TA Instruments, product name: DSCQ2000) according to the following method, and then the glass transition temperature was determined. That is, the above measurement sample was crushed, 5 mg was taken, placed in an aluminum pan, sealed with a lid, held at 120°C for 5 minutes, and then cooled. After that, the temperature was increased from -100°C to +120°C at a rate of 10°C / min. The glass transition temperature (Tg) was determined as the temperature at the intersection of a straight line extending from the low-temperature baseline of the obtained curve to the high-temperature side and a tangent drawn at the point where the gradient of the curve in the step-like change portion of the glass transition is maximum.
[0091] Example 1 100 parts by mass of binder resin (A1) (calculated as active ingredient excluding solvent, the same applies below), 135 parts by mass of epoxy resin (BL1), and 5.4 parts by mass of cationic polymerization initiator (C1) were diluted with methyl ethyl ketone to prepare a resin composition (1) having an active ingredient concentration of 40% by mass. This resin composition (1) was applied onto the release-treated surface of a release film (manufactured by Lintec Corporation, product name: SP-PET752150), and the resulting coating was dried at 100° C. for 2 minutes to form a sheet-like adhesive having a thickness of 5 μm. The release-treated surface of another release film (manufactured by Lintec Corporation, product name: SP-PET381031) was attached onto this sheet-like adhesive to produce a sheet-like adhesive (1) with a release film.
[0092] [Examples 2 to 6, Comparative Examples 1 to 4] Sheet adhesives (2) to (10) with release films were prepared in the same manner as in Example 1, except that the components constituting the sheet adhesive were those shown in Table 1.
[0093] The following tests were carried out on the sheet-like adhesives with release films (1) to (10) obtained in Examples 1 to 6 and Comparative Examples 1 to 4. The results are shown in Table 1.
[0094] [Storage shear modulus (G') of cured sheet adhesive] The storage shear modulus (G') of the cured product of the sheet-like adhesive was measured by a torsional shear method using a viscoelasticity measuring device (manufactured by Anton Paar, product name: MCR302) in accordance with JIS K7244-6. The details of the measurement method are shown below. (Preparation of measurement samples) After peeling off the release sheet from the sheet-like adhesive with release film obtained in the Examples and Comparative Examples, the sheet-like adhesive was stacked to obtain a laminate with a thickness of 0.5 mm. The obtained laminate of sheet-like adhesives was irradiated with UV light to cure the laminate made of the sheet-like adhesive. After UV irradiation, the laminate was heated at 100°C for 60 minutes to promote the curing reaction, and a cured product of the sheet-like adhesive (laminate) was obtained. The UV irradiation was performed using a high-pressure mercury lamp manufactured by iGraphics Co., Ltd., with an illuminance of 200 mW / cm 2 , cumulative light intensity 1000mJ / cm 2 The light intensity was measured under the following conditions. The light intensity meter used was UVPF-A1 manufactured by iGraphics. The cured sheet adhesive (laminate) was punched out into a cylindrical body with a diameter of 8 mm (height of 0.5 mm) and used as a measurement sample. (Measurement of storage shear modulus (G')) The storage shear modulus (G') of the obtained specimen was measured under the conditions of a frequency of 1 Hz, a test start temperature of -20°C, a test end temperature of +150°C, and a heating rate of 3°C / min. The values at 0°C and 100°C are shown in Table 1.
[0095] The cured products of the sheet-like adhesives (laminates) obtained in Comparative Examples 1 and 2 had storage shear moduli that were too high, and therefore slippage occurred when using the torsional shear method described above, making measurement impossible. Therefore, for the cured products of the sheet-like adhesives (laminates) obtained in Comparative Examples 1 and 2, the storage modulus (E') was measured in accordance with JIS K7244-4 (1999) using a dynamic viscoelasticity measuring device (TA Instruments, DMAQ800), and the storage shear modulus (G') was calculated from the approximation formula "E' = 3G'". The details of the method for measuring the storage modulus (E') are shown below. (Preparation of measurement samples) A cured sheet-like adhesive (laminate) was obtained in the same manner as above, and then the cured sheet-like adhesive (laminate) was cut into a size of 30 mm in length and 5 mm in width to serve as a measurement sample. (Measurement of storage modulus (E')) Using the obtained measurement sample, the storage modulus (E') was measured under conditions of a frequency of 1 Hz, a test start temperature of -20°C, a test end temperature of 150°C, and a heating rate of 3°C / min.
[0096] (Measurement of total light transmittance) The release film (light release film, manufactured by Lintec Corporation, product name: SP-PET381130) was peeled off from the sheet-like adhesive with release film obtained in the examples and comparative examples, and the exposed sheet-like adhesive was laminated to glass. The other release film was then peeled off, and the sheet-like adhesive was cured under the same conditions as above to obtain a measurement sample. After background measurement was performed using glass, the total light transmittance was measured using the obtained measurement sample in accordance with JIS K7361-1:1997.
[0097] (Haze value measurement) The release film (light release film, manufactured by Lintec Corporation, product name: SP-PET381130) was peeled off from the sheet-like adhesive with release film obtained in the examples and comparative examples, and the exposed sheet-like adhesive was laminated to glass. The other release film was then peeled off, and the sheet-like adhesive was cured under the same conditions as above to obtain a measurement sample. After background measurement was performed using glass, the haze value was measured in accordance with JIS K7136:2000 using the obtained measurement sample.
[0098] (peel test) The sheet-like adhesive with release film obtained in the Examples and Comparative Examples was processed into a size of 150 mm length and 50 mm width to obtain a test piece. A 180° peel test was performed on the obtained test piece by peeling off the release film (light release film, manufactured by Lintec Corporation, product name: SP-PET381130) at a speed of 300 mm / min. In this case, it was marked as ◯ when only the peeled off release film was peeled off, and marked as × when the sheet-like adhesive was torn and the adhesive was attached to the peeled off release film. Note that the sheet-like adhesive with the release film of Comparative Example 4 produced defects in this test, but in each of the above measurements, only the parts that were successfully peeled off were used for the measurements.
[0099] [Table 1]
[0100] The following can be seen from Table 1: The sheet adhesives (1) to (6) obtained in Examples 1 to 6 satisfy the low-temperature elastic modulus requirement. That is, the storage shear modulus (G'0) at 0°C of the cured products of the sheet adhesives (1) to (6) is 2×10 7 Pa or less. Therefore, the cured products of the sheet-like adhesives (1) to (6) have high flexibility at low temperatures. In addition, the cured products of the sheet-like adhesives (1) to (6) have a storage shear modulus (G' 100 ) is high, so the difference between the flexibility under low temperature conditions and the flexibility under high temperature conditions is small. Furthermore, the cured products of the sheet-like adhesives (1) to (6) also have excellent transparency. Furthermore, sheet adhesives that satisfy the low-temperature elastic modulus requirements tend to have poor shape retention, but because sheet adhesives (1) to (6) contain component (A), the release film alone can be peeled off cleanly in a peel test, and they have good shape retention. On the other hand, the sheet adhesives (7) to (9) obtained in Comparative Examples 1 to 3 do not satisfy the low-temperature elastic modulus requirement, and the cured products thereof have poor flexibility at low temperatures. The sheet adhesive (10) obtained in Comparative Example 4 satisfies the low-temperature elastic modulus requirements, has excellent flexibility, and the difference between the flexibility under low-temperature conditions and the flexibility under high-temperature conditions is small. However, because the sheet-like adhesive (10) does not contain component (A), the release film cannot be peeled off cleanly in a peel test, and the shape retention is poor. In addition, the cured product of the sheet-like adhesive (10) is poor in transparency.
Claims
1. An optical sheet-like adhesive comprising the following components (A) and (B): 0 ) is 2 x 10 7 An optical sheet adhesive having a viscosity of 100 Pa or less. Component (A): a binder resin component containing a binder resin having a glass transition temperature (Tg) of 50° C. or higher Component (B): an epoxy-based curable component containing a multifunctional epoxy resin
2. 2. The optical sheet-like adhesive according to claim 1, wherein at least one of the resins constituting component (A) and having a glass transition temperature (Tg) of 50° C. or higher is a phenoxy resin.
3. 3. The optical sheet-like adhesive according to claim 1, wherein at least one of the resins constituting the component (A) and having a glass transition temperature (Tg) of 50° C. or higher is a polyvinyl acetal resin.
4. The optical sheet-like adhesive according to any one of claims 1 to 3, wherein at least one of the multifunctional epoxy resins constituting component (B) is an epoxy resin (BL) that gives a cured product having a glass transition temperature (Tg) of 25°C or lower.
5. 5. The optical sheet adhesive according to claim 4, wherein the content of the epoxy resin (BL) is 50 to 75 mass % based on the total mass of the optical sheet adhesive.
6. The optical sheet-like adhesive according to claim 4 or 5, wherein the epoxy resin (BL) is a multifunctional epoxy resin having an oxyalkylene structure.
7. 7. The optical sheet-like adhesive according to claim 1, wherein at least one of the polyfunctional epoxy resins constituting the component (B) is liquid at 23°C.
8. 8. The optical sheet adhesive according to claim 1, wherein the haze of a cured product of the optical sheet adhesive is 1% or less.
Citation Information
Patent Citations
Optical waveguide-forming epoxy resin composition, optical waveguide-forming curable film, optical-transmitting flexible printed wiring board, and electronic information device
JP2010230944A
Active energy ray-curable type composition for optical film or sheet and active energy ray-curable type adhesive film or sheet
JP2010275373A
Epoxy resin composition
JP2013087124A
Radiation-curable adhesive, radiation-curable adhesive layer, radiation-curable adhesive sheet and laminate
JP2014043543A
Radiation-curable adhesive, radiation-curable adhesive layer, radiation-curable adhesive sheet and laminate
JP2017082228A